2016
DOI: 10.1093/mmy/myw115
|View full text |Cite
|
Sign up to set email alerts
|

In vitrosusceptibility of the oomycetePythium insidiosumto metallic compounds containing cadmium, lead, copper, manganese or zinc: Table 1.

Abstract: Pythium insidiosum is an aquatic oomycete that causes pythiosis, an important and severe disease of difficult treatment that affects humans, domestic and wild animals. This infection is often described in horses in Brazil and humans in Thailand. In clinical practice, we have observed many cases that do not respond to available therapies, indicating the need to explore alternative therapeutic approaches. In this sense, studies using metal compounds in conjunction with available antimicrobial agents have been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Among the heavy metals analyzed, the concentration of cadmium was the only one that showed a significant relationship with oomycete distribution. The toxicity of cadmium for soil microbial biomass growth and metabolic activity is well-known ( Xu et al, 2013 ) and Cd 2+ concentrations has been demonstrated to affect soil microbial diversity ( Chien et al, 2008 ; Ribeiro et al, 2016 ). Several studies have also demonstrated the effect of Cadmium on P. australis fitness ( Ederli et al, 2004 ) and in RDBS ( Lastrucci et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the heavy metals analyzed, the concentration of cadmium was the only one that showed a significant relationship with oomycete distribution. The toxicity of cadmium for soil microbial biomass growth and metabolic activity is well-known ( Xu et al, 2013 ) and Cd 2+ concentrations has been demonstrated to affect soil microbial diversity ( Chien et al, 2008 ; Ribeiro et al, 2016 ). Several studies have also demonstrated the effect of Cadmium on P. australis fitness ( Ederli et al, 2004 ) and in RDBS ( Lastrucci et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…Nesse sentido, destacam-se as pesquisas com fármacos da classe dos antibacterianos (ITAQUI et al, 2016;JESUS et al, 2016;BAGGA et al, 2018;CHATTERJEE;AGRAWAL, 2018;LORETO et al, 2018), antifúngicos, tais como: caspofungina, micafungina, terbinafina (PEREIRA et al, 2007ZANETTE et al, 2015;ITAQUI et al, 2016) óleos essenciais e compostos naturais (FONSECA et al, 2015a, ARAUJO;BOSCO;SFORCIN, 2016;VALENTE, 2016a, b;), nanocompostos (VALENTE et al, 2016a); nanopartículas de prata (bio-AgNP) (VALENTE et al, 2018) e compostos metálicos (RIBEIRO et al, 2017).…”
Section: Tratamentounclassified
“…However, miltefosine showed a favorable response in the rabbit model of pythiosis [151]. Copper acetate and cadmium acetate are metal compounds that exhibited anti-P. insidiosum activity with MICs of 4-64 and 16-256 μg/ml, respectively [152].…”
Section: Other Anti-p Insidiosum Substancesmentioning
confidence: 99%